2008
DOI: 10.1021/ja802377k
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Minimal Size Sensor Array for Metal Ion Detection

Abstract: The focus of this study was to demonstrate that, in the luminescent sensors, the signal transduction may possibly be the most important part in the sensing process. Rational design of fluorescent sensor arrays for cations utilizing extended conjugated chromophores attached to 8-hydroxyquinoline is reported. All of the optical sensors utilized in the arrays comprise the same 8-hydroxyquinoline (8-HQ) receptor and various conjugated chromophores to yield a different response to various metal cations. This is bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
194
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(196 citation statements)
references
References 56 publications
2
194
0
Order By: Relevance
“…Because many heavy-metal ions form insoluble hydroxides at high pH, we studied the spectroscopic properties of indicators 1-3 in the presence of heavy-metal ions at pH = 6.5. [20] Upon addition of Cd 2+ to a dilute solution of 1, its absorption and emission maxima shifted from 484 nm to 530 nm and from 556 nm to 550 nm, respectively; and the emission efficiency nearly quintupled as evidenced by the emission intensity upon excitation at the isosbestic point (510 nm), as shown in Fig. 1a.…”
Section: Rational Design Of the Indicatorsmentioning
confidence: 88%
See 1 more Smart Citation
“…Because many heavy-metal ions form insoluble hydroxides at high pH, we studied the spectroscopic properties of indicators 1-3 in the presence of heavy-metal ions at pH = 6.5. [20] Upon addition of Cd 2+ to a dilute solution of 1, its absorption and emission maxima shifted from 484 nm to 530 nm and from 556 nm to 550 nm, respectively; and the emission efficiency nearly quintupled as evidenced by the emission intensity upon excitation at the isosbestic point (510 nm), as shown in Fig. 1a.…”
Section: Rational Design Of the Indicatorsmentioning
confidence: 88%
“…Various sensor arrays for heavy-metal-ion detection using commercial or custom fluorescent indicators have been reported that manifest remarkable selectivity at mM concentrations of the ions. However, extending this performance to the environmentally relevant M concentrations remains a challenge because of the lack of suitable fluorescent indicators [3,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, it has found application in the sensing of various analytes including cations [70][71][72], anions [73], electroneutral small molecules such as amino acids [74], saccharides [75,76], explosives [77], poisonous gases [78], peptides [79] and proteins [80,81], consumer products including sweeteners [82], beverages [26,70,83], and toothpastes [73], and so on.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…13,14 Mercury represents for one of the most toxic heavy metals due to its thiophilic nature to proteins and enzymes. [15][16][17][18] Exposure to Hg 2+ leads to irreversible damage and dysfunction in biosystems, including brain, stomach, kidney, and central nervous system. 19,20 What is more worrisome is that Hg 2+ may exist in air, water and soil.…”
Section: Introductionmentioning
confidence: 99%